Prenatal paternal stress predicts infant parasympathetic functioning above and beyond maternal prenatal stress. (2nd November 2022) - Gao, Mengyu; Brown, Mindy A.; Neff, Dylan; Crowell, Sheila E.; Conradt, Elisabeth
ABSTRACT: Background: Paternal stress is often assessed by maternal report and is posited to influence infant development indirectly by contributing to a mother's stress and experiences during pregnancy. Far less is known about how direct effects of prenatal paternal stress, as described by fathers themselves, are related to an infant's physiological functioning. We assessed fathers' own experiences of stress and examined its direct impact on infant respiratory sinus arrhythmia (RSA), a biological index of self-regulation, at seven-month postpartum. Method: During the third trimester of pregnancy, the UCLA Life Stress Interview was conducted to assess chronic stress in mothers and fathers ( N = 90). Infant baseline RSA and RSA reactivity in response to the Still-Face paradigm were assessed at seven-month postpartum. Results: Infants of fathers with high prenatal stress showed lower baseline RSA, possibly reflective of poor infant psychophysiological regulation. The predictive role of paternal stress remained significant after controlling for maternal stress. Conclusions: Our findings provide emerging empirical evidence to support the influence of prenatal paternal stress on infant RSA, highlighting the important role of fathers for child development.